Coffee and tea consumption and the risk of glioma: a systematic review and dose–response meta-analysis. Issue 1 (14th January 2022) - Pranata, Raymond; Feraldho, Andrea; Lim, Michael Anthonius; Henrina, Joshua; Vania, Rachel; Golden, Nyoman; July, Julius
Abstract: In this systematic review and dose–response meta-analysis, we aimed to assess whether coffee and tea consumption is related to the risk of glioma. We performed a systematic literature search using PubMed, Embase, Scopus and the EuropePMC from the inception of database up until 1 October 2020. Exposures in the present study were coffee and tea consumption, the main outcome was the incidence of glioma. The present study compares the association between the exposure of coffee and tea with the incidence of glioma, and the results are reported in relative risks (RR). There are 12 unique studies comprising of 1 960 731 participants with 2987 glioma cases. Higher coffee consumption was associated with a statistically non-significant trend towards lower risk of glioma (RR 0·77 (95 % CI 0·55, 1·03), P = 0·11; I 2 :75·27 %). Meta-regression showed that the association between coffee and glioma was reduced by smoking ( P = 0·029). Higher tea consumption was associated with a lower risk of glioma (RR 0·84 (95 % CI 0·71, 0·98), P = 0·030; I 2 :16·42 %). Sensitivity analysis by removal of case–control studies showed that higher coffee consumption (RR 0·85 (95 % CI 0·72, 1·00), P = 0·046; I 2 :0 %) and higher tea consumption (RR 0·81 (95 % CI 0·70, 0·93), P = 0·004; I 2 :0 %, P non-linearity = 0·140) were associated with lower risk of glioma. Dose–response meta-analysis showed that every one cup of coffee per day decreases the risk of glioma by 3 % (RR 0·97 (95 % CI 0·94, 0·99), P = 0·016, P non-linearity = 0·054) and every one cup of tea per day decreases the risk of glioma by 3 % (RR 0·97 (95 % CI 0·94, 1·00), P = 0·048). This meta-analysis showed apparent association between coffee and tea intake and risk of glioma.